A ordem do discurso sobre a imagem visual na modalidade da educação de jovens e adultos no Brasil - Silva, Maria Lúcia Gomes da (2019)
In contemporary society, we live under the aegis of the visual image. In our daily life, the genres of photography, drawing, painting, billboard, cartoon, print, mediated by the technological apparatus of the computer, television, cinema, DVD, smartphone, among others, record information, provide entertainment and represent sociocultural contexts that intentionally affect our sensations, perceptions, values, senses and meanings. In this scenario, the visual image both educates the individuals and constitutes an object of reflection and investigation. The game of relations among visual image, Education and discourse led me to the study of the object: the order of the discourse about the visual image in the modality of Youth and Adult Education in Brazil. The research advocated the thesis that the visual image is a discursive constituent of the Youth and Adult Education and its goal was to analyze the discourse order on the visual image in in the modality of the Youth and Adult Education in Brazil. The study adopted the theoreticalmethodological approach of Michel Foucault's Archaeological Analysis of Discourse (AAD), whose theory made it possible to know the rules of operation of the investigated discursive order by disposing the relations of the enunciations. The archaeological investigation has taken place on the terrain of language. The research steps were the mapping and the enunciative analysis of the documents, the National Curriculum Guidelines for Youth and Adult Education (2000), and the Operational Guidelines for Youth and Adult Education (2010). In these documents and in the subsequent ones, in which I worked with the archaeological procedures of excavation, analysis and description of the enunciations, I obtained the research results and I envisaged an educational discursive order, in which the found enunciative series demonstrated the visual image and occupied status in the literacy process, whose presence and function depend on the literacy model adopted in different periods; a second discursive order, the pedagogical one, showed the image presence in the initial, continuing and permanent training processes of the Youth and Adult Education educators, grounding the pedagogical teaching practice; and, finally, the sociocultural discursive order, in which the visual image represents an access code for the citizenship practice and a formation instrument of the critical awareness and cultural appreciation. The observation of these discursive orders (educational, pedagogical and sociocultural) about the visual image of the Youth and Adult Education made possible to corroborate this thesis, and it demonstrated the study legitimacy in the production of knowledge in the research area in education.